History of vaccines - Plotkin, Stanley (Henry Stewart Talks, 2015)
History of vaccines, The impact of vaccination, Variolation, Pasteur and first real vaccines, Inactivated vaccines at the end of the 19th Century, Toxoids, Attenuation by serial passage, Viruses grown in cell culture, Genetic engineering and recombinant vaccines, Vaccines licensed since 2000, Cumulative number of vaccines developed